Case Report: “Methicillin-Resistant Staphylococcus aureus Endocarditis Overlying Calcified Mitral Annular Abscess Misdiagnosed as Klebsiella pneumoniae Endocarditis” - Yamamoto, Hiroyuki; Hashimoto, Katsuya; Yamada, Hiroyuki; Ikeda, Yoshihiko; Takahashi, Takashi; Hashimoto, Toru (Frontiers in Microbiology, 2022)
Infective endocarditis (IE) involving mitral annular calcification (MAC) is a rare disease, but is potentially lethal due to frequent serious periannular complications, and therefore requires early diagnosis and prompt treatment. However, either reaching the correct diagnosis or the detection of periannular complications, even with conventional transesophageal echocardiography (TEE), remains challenging because calcium deposition obscures clear visualization of the area around the MAC. We describe a unique case of methicillin-resistant Staphylococcus aureus (MRSA) IE involving a calcified mitral annular abscess, which was initially misdiagnosed as Klebsiella pneumoniae IE. Accurate diagnosis of MAC-related IE as well as detection of the annular abscess were made possible by 4D TEE, leading to successful cardiac surgery, which confirmed MRSA IE pathologically, and the associated annular abscess. This case highlights the usefulness of 4D TEE for the accurate diagnosis and proper surgical planning. In addition, this case raises the limitations of the modified Duke criteria in cases of definite IE with dual bacteremia.